Implementasi Metode Demonstrasi pada Mata Pelajaran Matematika Siswa Kelas IV SD Negeri 31 Jati Tanah Tinggi Padang - Lili Rismaini; Ulhusna , Mishbah; Dewimarni , Syelfia (Pekodimas : Jurnal Pengabdian Kepada Masyarakat, 2026)
This Community Service (PKM) is one form of Tridharma of Higher Education. This PKM is proposed to carry out activities that are the implementation of demonstration methods in mathematics subjects. This activity is proposed with the consideration that there is still a lack of student knowledge about demonstration methods in mathematics lessons. Therefore, with this PKM activity, it can make it easier for students to face mathematics learning. Activities in the form of coaching, socialization and education that have been carried out at SD Negeri 31 Jati Tanah Tinggi have run smoothly in accordance with the desired targets and outcomes. Based on the results of the socialization of mathematics learning through the Implementation of Demonstration Methods in Mathematics Subjects for Grade IV Students of SD Negeri 31 Jati Tanah Tinggi Padang provide benefits that can eliminate student boredom in learning mathematics, provide variety at SD Negeri 31 Jati Tanah Tinggi Padang. This means that there is a significant influence on the socialization of mathematics learning through the Implementation of Demonstration Methods in Mathematics Subjects for Grade IV Students of SD Negeri 31 Jati Tanah Tinggi Padang. Keywords: implementation, demonstration method, mathematics